Aerial jurisdiction over safety zones surrounding maritime installations - Gough, Malcolm P (Department of Public Law, 2021)
Extending the search for oil and gas into the marine areas is a relatively recent phase in the production of oil and gas. Although shallow water mining has been conducted since the 1940's, these attempts have been seen more as extensions of terrestrial mining than as serious offshore attempts. The technological feasibility of offshore oil ~nd gas mining has increased rapidly from the late 1950's onwards. 2This coincides, and more often than not is related to, recent vast developments in the Law of the Sea and pursuit of agreement by nations on vital questions related to the use and control of the sea. International law relating to the offshore oil and gas regime is therefore fairly recent in origin and, in many areas, unsettled. Lawyers have wrestled with the problems of creating a legal regime in areas beyond State sovereignty, applicable to constrictions which generally do not adequately resemble, for legal purposes, either ships or islands. In addition to the regime to be applied to the installation itself, it was soon realized that special precautions would have to be taken to ensure that loss of both life and property was kept to an absolute minimum. Offshore installations represent vast investment. _They operate on, and are exposed to, an environment which is unpredictable, powerful and on occasion violent in nature, not to mention the nature of the substances to be brought to the surface, which are dangerous, as experience has shown, in terms of inter alia, volatility and threat of pollution. One of the concepts soon arrived at was that of the safety zone, which has the obvious purpose of minimizing the possibility of collision with the installation, or crafts or objects attached to, or in the service of, the installation. Now as the concept of a safety zone suggests, and due to the fact that the installations frequently operate beyond territorial waters, it was obvious that parts of the high seas were to be affected. While uneasy agreement has been reached in the conventions on the Law of -the Sea~ in relation to shipping and respect for safety zones, the concept of aerial jurisdiction over these legally unique areas still remains a controversial one. This despite the fact that overflight of these areas is both possible and likely by almost all aircraft, and that certain aircraft, particularly helicopters, have proven vital to the operation of installations, as a means of transport and communication. In addition technology has provided, and will provide, new craft which will be classified either as ships or aircraft, and will be considered in the light of their usefulness to oil and gas installations or alternatively the threat they pose to them.